2020
DOI: 10.3389/fgene.2020.00929
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA Colon Cancer-Associated Transcript-1 Promotes Migration, Invasion, and Epithelial Mesenchymal Transition of Lung Adenocarcinoma by Suppressing miR-219-1

Abstract: Previous evidence suggests that long non-coding colon cancer-associated transcript-1(CCAT1) plays a pivotal role in the progression of a variety of tumors. However, little is known about its role in lung adenocarcinoma (LAD). In this study, we found LAD tissue samples had a higher expression of CCAT1 but a lower expression of miR-219-1 compared to their adjacent non-tumor tissues. CCAT1 negatively regulated the expression of miR-219-1. miR-219-1 suppressed the proliferation of A549 and H1299 cells. Knockdown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To validate the capacity of the PH probe for identifying enhancer activity, we designed corresponding sequences of the PH probe targeting the enhancer that regulates the expression of CCAT 1 (“ CCAT 1 enhancer” for short) (Table S2). The CCAT 1 is a long noncoding RNA, which participates in the promotion of tumor invasion and metastasis. Its abnormally high expression in tumors has been reported to be associated with enhancer activation . Since P2 is employed as the specific sequence to open the hairpin structure of H1 and initiate subsequent signal amplification, we verified the capacity of H1 and H2 probes for identifying the sequence P2 in a buffer solution (Figure B).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…To validate the capacity of the PH probe for identifying enhancer activity, we designed corresponding sequences of the PH probe targeting the enhancer that regulates the expression of CCAT 1 (“ CCAT 1 enhancer” for short) (Table S2). The CCAT 1 is a long noncoding RNA, which participates in the promotion of tumor invasion and metastasis. Its abnormally high expression in tumors has been reported to be associated with enhancer activation . Since P2 is employed as the specific sequence to open the hairpin structure of H1 and initiate subsequent signal amplification, we verified the capacity of H1 and H2 probes for identifying the sequence P2 in a buffer solution (Figure B).…”
Section: Resultsmentioning
confidence: 77%
“…To test the capacity of the platform for intranuclear interrogation of enhancer activity in living cells, we selected two types of human lung cancer cell lines, which have been reported with high CCAT 1 enhancer activity, i.e., A549 and H1975, and one type of human lung fibroblast cell line with low CCAT 1 enhancer activity cell, i.e., MRC5. ,, In our work, we identified enhancer activity in living cells, which cannot be achieved using traditional methods that require cell lysis (dead cells). Therefore, we used qPCR to detect the expression of the CCAT 1 gene, which is regulated by CCAT 1 enhancer activity (Figure S6A,B).…”
Section: Resultsmentioning
confidence: 99%
“…To date, many studies have revealed that miR-219a functions as a tumour suppressor in different cancers, such as ovarian and breast cancer ( Long et al, 2017 ; Xing et al, 2018 ; Wang et al, 2020 ; Ye et al, 2021 ). In the current study, we predicted that miR-219a could target integrins (ITGA and ITGB) which can participate in the activation of the PI3K/Akt signalling pathway.…”
Section: Discussionmentioning
confidence: 99%